Partnership Concept of Milk Processing Industry with Milk Producing Cooperatives for Prosperity Dairy Farmers - Widaningsih, Widaningsih; Suhariningsih, Suhariningsih; Sihabuddin, Sihabuddin; Santoso, Budi (Technium Social Sciences Journal, 2021)
The management of dairy farming in Indonesia is considered not optimal, it can be seen from the insufficient domestic consumption of fresh milk, even though the productivity of fresh milk always increases every year. The government’s action to import milk from abroad to meet the needs of fresh milk has caused a decrease in domestic productivity and availability of fresh milk, which in turn has an impact on the unfulfilled welfare of dairy farmers. The partnership between the milk processing industry and cooperatives is carried out in an effort to realize the welfare of dairy farmers. Besides having to fulfill the legal requirements of the agreement, a partnership must also contain clear, balanced, and fair clauses for the parties